2015
DOI: 10.1101/gad.264036.115
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial function downstream from KDM5A histone demethylase rescues differentiation in pRB-deficient cells

Abstract: The retinoblastoma tumor suppressor protein pRb restricts cell growth through inhibition of cell cycle progression. Increasing evidence suggests that pRb also promotes differentiation, but the mechanisms are poorly understood, and the key question remains as to how differentiation in tumor cells can be enhanced in order to diminish their aggressive potential. Previously, we identified the histone demethylase KDM5A (lysine [K]-specific demethylase 5A), which demethylates histone H3 on Lys4 (H3K4), as a pRB-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 63 publications
8
63
0
1
Order By: Relevance
“…Similarly to our work, mitochondrial respiration has been identified as a target of JARID1A repression in mouse embryonic fibroblasts, where JARID1A knockdown restores the ability of cells lacking Retinoblastoma tumor suppressor protein function to differentiate in a manner that is dependent on its demethylase activity37. In a finding that is superficially at odds with our results and those from human cells, in Drosophila melanogaster , Lid, the sole JARID ortholog present in this organism, functions to activate mitochondrial genes in a manner that is independent of its enzymatic activity38.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly to our work, mitochondrial respiration has been identified as a target of JARID1A repression in mouse embryonic fibroblasts, where JARID1A knockdown restores the ability of cells lacking Retinoblastoma tumor suppressor protein function to differentiate in a manner that is dependent on its demethylase activity37. In a finding that is superficially at odds with our results and those from human cells, in Drosophila melanogaster , Lid, the sole JARID ortholog present in this organism, functions to activate mitochondrial genes in a manner that is independent of its enzymatic activity38.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, in fibroblastic models RB loss is associated with increased glutamine utilization (Clem and Chesney, 2012; Reynolds et al, 2014), and loss of RBF has been associated with altered glutamine catabolism in drosophila (Nicolay et al, 2013). Recent studies have shown that loss of RB can lead to decreased oxidative phosphorylation and more dependency on glycolytic metabolism (Nicolay et al, 2015; Varaljai et al, 2015). Consonantly, E2F1 and RB in tissue can provide a critical node of regulation between proliferation and metabolic activity (Blanchet et al, 2011; Lopez-Mejia and Fajas, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A similar role for JARID1C is suggested by the brain-specific expression in Zebrafish embryos and neural defects following its knockdown [86]. JARID1 proteins are also implicated in later development and adult tissue homeostasis, including myogenic differentiation of embryonic fibroblasts [111]. A role for JARID1B in postnatal mammary gland development was observed in a viable strain of JARID1B knockout mice [33] and mice where only JARID1B’s ARID domain was deleted [106].…”
Section: Overview Of Jarid1 Family Functionmentioning
confidence: 87%